2016
DOI: 10.1371/journal.pone.0167020
|View full text |Cite
|
Sign up to set email alerts
|

Equol Attenuates Atherosclerosis in Apolipoprotein E-Deficient Mice by Inhibiting Endoplasmic Reticulum Stress via Activation of Nrf2 in Endothelial Cells

Abstract: The development of atherosclerosis is closely related to excessive endoplasmic reticulum stress (ERs). Equol reportedly protects against cardiovascular disease; however, the underlying mechanism for this protection remains unknown. Herein, the mechanisms contributing to the atheroprotective effect of equol were addressed using apolipoprotein E knockout (apoE-/-) mice fed a high-fat diet (HFD) with or without equol. Equol intervention reduced atherosclerotic lesions in the aorta in HFD-fed apoE-/- mice. Plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 56 publications
(64 reference statements)
1
20
0
Order By: Relevance
“…On the other hand, Nrf2 signaling pathway is the main antioxidant response element pathway and studies has affirmed that Nrf2 could be activated by DHM [24,55]; therefore, modulation of the Nrf2 signaling pathway may be a potential mechanism underlying the protective effects promoted by the intake of DHM. Nrf2 signaling pathway regulates the cellular redox homoeostasis and cytoprotective responses, allowing adaptation and survival under conditions of stress, which could be triggered by different treatments inducing ROS formation and antioxidants such as DHM [55] and S-(-)Equol [56]. According to the previous reports, the regulation of PA on Nrf2 signaling is closely related to the processing time and its concentration, and these ROS inducers including PA, H 2 O 2 , UVB, and LPS etc could contribute to cell survival by inducing Nrf2 activation under short time and low level treatment conditions, while excessive exposure to these inducers would inhibit Nrf2 signaling and thus trigger death.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Nrf2 signaling pathway is the main antioxidant response element pathway and studies has affirmed that Nrf2 could be activated by DHM [24,55]; therefore, modulation of the Nrf2 signaling pathway may be a potential mechanism underlying the protective effects promoted by the intake of DHM. Nrf2 signaling pathway regulates the cellular redox homoeostasis and cytoprotective responses, allowing adaptation and survival under conditions of stress, which could be triggered by different treatments inducing ROS formation and antioxidants such as DHM [55] and S-(-)Equol [56]. According to the previous reports, the regulation of PA on Nrf2 signaling is closely related to the processing time and its concentration, and these ROS inducers including PA, H 2 O 2 , UVB, and LPS etc could contribute to cell survival by inducing Nrf2 activation under short time and low level treatment conditions, while excessive exposure to these inducers would inhibit Nrf2 signaling and thus trigger death.…”
Section: Discussionmentioning
confidence: 99%
“…ERS can activate many signal pathways, PERK-eIF2α-ATF4 signaling pathway (He et al, 2016 ), PI3K-Akt-NOS pathway (Alexaki et al, 2004 ), PERK-eIF2α-CHOP signaling (Gu et al, 2017 ), IRE1α-ASK1-JNK pathway (Kong et al, 2017 ), and IRE1α-ASK1-P38 pathway (Kong et al, 2017 ) have been confirmed to be involved in ERS mediated apoptosis. And Nrf2, plays an important role in oxidative stress, also involved in ERS-mediated apoptosis (Zhang et al, 2016 ; Wang et al, 2017 ). H 2 S has been confirmed to inhibit oxidative stress and inflammation, and relevant signal pathways have crosstalk with these above signals.…”
Section: Discussionmentioning
confidence: 99%
“…Equol is more bioactive than daidzein in terms of anti‐oestrogenic activity, antioxidant capacity, and anti‐cancer effects (Arques, Rodriguez, Langa, Landete, & Medina, ). Equol treatment in ApoE −/− mice fed with high‐fat diet (HFD) reduces atherosclerotic lesions in the aorta, reduces triglycerides, total cholesterol, and LDL cholesterol, and increases HDL cholesterol (Zhang et al, ).…”
Section: Gut Microbiota‐derived Active Metabolites Of Polyphenolsmentioning
confidence: 99%